Language Learning Strategies: Contrasting English Department and Non-English Department Students - Sheila Agustina (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2022)
It is a fact that language learning strategies can help learners to learn a language successfully. English learners who employ certain language learning strategy are believed to be able to master the language better and faster than those who do not employ any strategies or those who are not aware of their learning strategies. While learning strategies may affect the success of a language learner, a learner’s ‘choice’ of certain strategy can be influenced by one’s study background. Some previous studies have verified it by examining language learning strategies used by students of English Department and students of non-English Department using Oxford’s Strategy Inventory for Language Learning (SILL). Thus, with the same instrument, this research aims to prove the presence of the students’ differences in using the strategies. This research is under a survey research design with students’ responses as the main data and questionnaires as the instrument. The finding indicates that English Department students make use of social strategies the most, while non-English Department students generally use metacognitive strategies. The implication of this research is to give valuable inputs for English lecturers of both settings in subjecting their students according to the findings of each strategy’s use.